CONCEPTUAL METAPHOR AS THE BASIS OF COGNITIVE MODELS - Ismagulova, G.B. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The article deals with the conceptual metaphor presented by J. Lakoff and M. Johnson as an interactive model based on the invariance principle. This idea was further developed by such scientists as Gerard Steen and Raymond Gibbs, M. Pielenz, which is also analyzed in this article.
Keywords: metaphor; cognitive models; source area; target area; theory; metaphorization